Answer:
Step-by-step explanation:
Answer:
y = 2x - 3
Step-by-step explanation:
y - - 3 = 2(x-0)
y + 3 = 2x
y = 2x -3
Answer:
- 48
Step-by-step explanation:
If you want to learn more about this concept, it's called composition of functions.
First, you plug in g(x) as if it were x into f(x).
f(g(x))= -5 (1/2x + 4) + 2
= -5/2x - 20 + 2
= -5/2x - 18
Then, plug in the value given, as x.
= -5/2 (12) - 18
= -30 - 18
= - 48
I hope this helped!
Answer:
Step-by-step explanation:
It is add three add three add three add three
Answer:
110 = 12
110 + 110 + 110 + 110 = 440
so 110 × 4 = 440
4 × 12 =<em><u> 48 days</u></em>
hope this helps